Assessment of the antifertility property of ocimum sanctum - Girisdan K (Department of Pharmacology and Toxicology, College of Veterinary and Animal Sciences, 1979)
A study was carried out in rats, to assess the antifertility property of the benzene fraction of the leaves of the plant Ocimum sanctum. Premating treatment was done in female animals at does levels of 200 and 400 mg per kilogram body weight for a duration of eight days. Male animals were subjected to the treatment at a dose level of 200 mg per kilogram body weight for 20 days . The experimental animals were allowed to mate with untreated animals of the opposite sex. Histopathological examination of the organs – pituitary, ovary, tests, liver and kidney were carried out.